The Wiley‐Blackwell Handbook of Childhood Social Development 2010
DOI: 10.1002/9781444390933.ch14
|View full text |Cite
|
Sign up to set email alerts
|

The Interplay Between Parents and Peers as Socializing Influences in Children's Development

Abstract: For the most part, separate research traditions have developed to study children ' s relationships with parents and peers. The organization and format of this handbook refl ect these separate and distinct literatures. Studies of children ' s interactions with their parents have focused on attachment security (see Chapter 17 ), parenting practices (see Chapter 18 ), and variations associated with demographic and cultural factors (see Chapters 8 and 9 ). As a quick perusal of these chapters reveals, a central is… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
8
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(9 citation statements)
references
References 67 publications
1
8
0
Order By: Relevance
“…Parents and peers communicate, model, and reinforce certain attitudes, which contributes to parent-child and peer-child attitudinal similarity. Parents are seen as the principal agent of socialization because they not only provide the norms of appropriate attitudes but also manage children’s environments, including their children’s interactions with peers (Grusec, 2011; Parke, Burks, Carson, Neville, & Boyum, 1994; Reich & Vandell, 2011). Whereas the definition of parents is often straightforward, the peer environment consists of crowds, cliques, and close friends, with close friends having the most influence (Brown & Klute, 2008).…”
Section: Theories Of Development Of Ethnic and Racial Attitudesmentioning
confidence: 99%
See 1 more Smart Citation
“…Parents and peers communicate, model, and reinforce certain attitudes, which contributes to parent-child and peer-child attitudinal similarity. Parents are seen as the principal agent of socialization because they not only provide the norms of appropriate attitudes but also manage children’s environments, including their children’s interactions with peers (Grusec, 2011; Parke, Burks, Carson, Neville, & Boyum, 1994; Reich & Vandell, 2011). Whereas the definition of parents is often straightforward, the peer environment consists of crowds, cliques, and close friends, with close friends having the most influence (Brown & Klute, 2008).…”
Section: Theories Of Development Of Ethnic and Racial Attitudesmentioning
confidence: 99%
“…On the other hand, research has shown that the lagged effects of parental prejudice are more stable than those of peers’ (Miklikowska, 2017), suggesting that long-term and obligatory relationships with parents have stronger effects than transitive peers. However, socialization literature shows that parents, in addition to direct effects, might also exert indirect effects by managing their children’s environments, selecting organizations they join, and monitoring their social interactions (Grusec, 2011; Parke et al, 1994; Reich & Vandell, 2011), making them overall more important than peers (Steinberg, 2001). In particular, parental attitudes might have consequences for the kind of peers youth associate with (i.e., less or more prejudiced).…”
Section: Limitations Of Extant Researchmentioning
confidence: 99%
“…As much as Miu Lan's story is about self-acceptance and expression, this text also demonstrates the ways in which peer socialization influences children's gender development (Reich & Vandell, 2011). Schools as sites of gender socialization, particularly through the inclusionary and exclusionary politics of the playground, are explored in this children's book, tracing the social ups and downs experienced by a young nonbinary protagonist who possesses visible differences in childhood gender expression from their peers.…”
Section: "Why Do I Have To Be Just One Thing?": Breaking Beyond the Bmentioning
confidence: 96%
“…Both fathers and mothers play an important role in the facilitation of their children's peer relationships by initiating informal contact between their own children and potential play partners, especially among young children (Reich and Vandell, 2011). However, from infancy through middle childhood, mothers are more likely to assume the managerial role than fathers (Parke, 2002).…”
Section: Parents As Managers Of Children's Opportunitiesmentioning
confidence: 99%